2022
DOI: 10.1021/acs.joc.1c03002
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Functionalized Azepinone Derivatives via a (4 + 3)-Cycloaddition of Vinyl Ketenes and α-Imino Carbenes Derived from N-Sulfonyl-triazoles

Abstract: An intermolecular RhII-catalyzed, formal (4 + 3)-cycloaddition between vinyl ketenes and N-sulfonyl-1,2,3-triazoles for the construction of azepinone products is described. Employing vinyl ketenes as a 1,4-dipolar surrogate, instead of the more commonly used dienyl moieties, allows for the intermolecular and selective formation of azepinone products over a potential (3 + 2)-cycloadduct under mild reaction conditions allows for the generation of azepinone products in up to 98% yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Shen and Xu successfully demon-Scheme 5. [3 + n] cycloadditions of sulfonyltriazole with heterocyclics [43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: [3 + N] Cycloadditions Of Sulfonyltriazole With Heterocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shen and Xu successfully demon-Scheme 5. [3 + n] cycloadditions of sulfonyltriazole with heterocyclics [43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: [3 + N] Cycloadditions Of Sulfonyltriazole With Heterocyclesmentioning
confidence: 99%
“…Specifically, cyclopropane 37 underwent ring opening to afford compound 38. The Ashfeld group reported an alternative approach to C-C bond cleavage within the ring [47]. They developed an intermolecular rhodium(II) catalyzed formal [4 + 3] cycloaddition reaction between vinyl ketenes 39 and triazoles.…”
Section: [3 + N] Cycloadditions Of Sulfonyltriazole With Heterocyclesmentioning
confidence: 99%
“…[48] The optimal conditions for this reaction were Very recently, Ashfeld's group developed a methodology for the preparation of azepinone derivatives 122 from vinyl ketenes 125 and N-sulfonyl-1,2,3-triazoles 120 (Scheme 32). [49] Various 1,4-dipolar surrogates are available for this intermolecular rhodium mediated (4 + 3)-cycloaddition, howbeit vinyl ketenes enriched favorable yield. After testing numerous catalysts, it was found that Rh 2 (Oct) 4 was most effective in dispensing the considered product azepinone 122.…”
Section: Rhodium-catalyzed Approachesmentioning
confidence: 99%